Norwegian Overnight Interbank Interest Rates - Q. Farooq Akram; Casper Christophersen (Norges Bank, 2011)
This paper addresses the lack of reliable information about overnight interest rates in the Norwegian interbank market. We infer actual interest rates from interbank transactions recorded in the real-time gross settlement (RTGS) system of Norges Bank over the period October 2006 - November 2010. We propose a new measure of overnight interest rates, NONIA, which may be calculated daily as a value-weighted average of overnight interest rates on individual loans. This may supplement information provided by indicative interest rates such as NIBOR. We also calculate an indicator based on dispersion of interest rates across individual loans and the spread between NONIA and the Norges Bank's overnight deposit rate. This indicator may be useful for assessing whether overnight interest rates are close to the central bank key policy rate.
hdl:11250/2507335
Keywords: G21; E42; E43; E58; 330; RTGS; interbank money market; interest rates